Region-Specific Effects of 10-Hz Transcranial Alternate Current Stimulation Over the Left Posterior Parietal Cortex and Primary Somatosensory Area on Tactile Two-Point Discrimination Threshold - Yokota, Hirotake; Otsuru, Naofumi; Saito, Kei; Kojima, Sho; Miyaguchi, Shota; Inukai, Yasuto; Nagasaka, Kazuaki; Onishi, Hideaki (Frontiers in Neuroscience, 2021)
Changes in α-band cortical oscillatory activity (8–13 Hz) affect perception; however, how these changes in the left posterior parietal cortex (PPC) and primary somatosensory cortex (S1), which play different roles in determining two-point discrimination (TPD) threshold, affect TPD threshold remain unelucidated. Therefore, to determine TPD threshold, we aimed to investigate the function of the left PPC and S1 by applying α-band transcranial alternating current stimulation (α-tACS; 10 Hz). TPD threshold was examined at the pad of the right index finger, contralateral to the stimulation site, in 17 healthy adults using a custom-made, computer-controlled, two-point tactile stimulation device, with random application of either active or sham α-tACS over the left PPC (Experiment 1) and left S1 (Experiment 2). Then, 50% TPD threshold was obtained in the active and sham conditions via logistic regression analysis. Afterward, we compared the difference between the active and sham conditions at 50% TPD threshold in each region and found that α-tACS reduced TPD threshold when applied over the left PPC (P = 0.010); however, its effect was insignificant when applied over the left S1 (P = 0.74). Moreover, a comparison of the change in 50% TPD threshold among the regions revealed that α-tACS applied over the left PPC significantly reduced TPD threshold compared with that applied over the left S1 (P = 0.003). Although, we did not reveal the actual changes in cortical activity induced by α-tACS, this is the first empirical evidence that α-tACS applied over the left PPC and left S1 exerts region-specific effects on determining TPD threshold assessed in the contralateral index finger pad to the stimulation.